2023
DOI: 10.3390/biom13050809
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Delivery Using a Collagen Membrane for Bone Tissue Regeneration

Abstract: The use of biomaterials and bioactive agents has shown promise in bone defect repair, leading to the development of strategies for bone regeneration. Various artificial membranes, especially collagen membranes (CMs) that are widely used for periodontal therapy and provide an extracellular matrix-simulating environment, play a significant role in promoting bone regeneration. In addition, numerous growth factors (GFs) have been used as clinical applications in regenerative therapy. However, it has been establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Collagen-based materials such as membranes, sponges, matrices, hydrogels, and composite scaffolds have been extensively used in in vivo studies to facilitate bone tissue regeneration. Takayama et al summarized growth factor (GF) delivery systems that use collagen membranes (CMs) for bone tissue regeneration [ 29 ]. Biomaterials and bioactive agents may play a potential role in bone defect repair; thus, they are being explored for developing bone regeneration strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen-based materials such as membranes, sponges, matrices, hydrogels, and composite scaffolds have been extensively used in in vivo studies to facilitate bone tissue regeneration. Takayama et al summarized growth factor (GF) delivery systems that use collagen membranes (CMs) for bone tissue regeneration [ 29 ]. Biomaterials and bioactive agents may play a potential role in bone defect repair; thus, they are being explored for developing bone regeneration strategies.…”
mentioning
confidence: 99%
“…Takayama et al highlighted the role of GF-containing CMs in bone tissue regeneration and discussed the use of these CMs in preclinical animal models of regeneration. Additionally, authors addressed the potential concerns and suggested future research directions for GF therapy in regenerative science [ 29 ].…”
mentioning
confidence: 99%